Dinamika Ketersediaan dan Kebutuhan Pangan Sumba Timur: Implikasi terhadap Ketahanan Pangan Daerah - Widiantini, Ni Putu Setita Praena; Wayan Damar Windu Kurniawan; I Gede Putu Eka Suryana; Umi Varica Sumadyanti; Oriza Mardiana (Jurnal ENMAP (Environment and Mapping), 2025)
East Sumba Regency faces challenges to food security due to geographical conditions, a dry climate, and socio-economic dynamics. This study aims to analyze the changes in food availability and demand between 2023 and 2029. A descriptive quantitative approach was employed, utilizing data on food production, population, and regional characteristics. The results show that although a food surplus existed in 2023, it is projected to decline by 2029 due to land degradation, climate change, population growth, and land-use change. Geographical factors such as topography, soil type, and water distribution significantly influence food production. In conclusion, strategies including the protection of productive land, the strengthening of irrigation systems, crop diversification, and the adoption of adaptive technologies are essential to enhance food security in the future.